2020
DOI: 10.3390/cancers12082098
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-Inducing Anticancer Therapies: From Global to Precision Damage

Abstract: DNA damage-inducing therapies are of tremendous value for cancer treatment and function by the direct or indirect formation of DNA lesions and subsequent inhibition of cellular proliferation. Of central importance in the cellular response to therapy-induced DNA damage is the DNA damage response (DDR), a protein network guiding both DNA damage repair and the induction of cancer-eradicating mechanisms such as apoptosis. A detailed understanding of DNA damage induction and the DDR has greatly improved our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 149 publications
(181 reference statements)
2
46
0
Order By: Relevance
“…In the same model, shikonin caused DNA damage [ 142 ] ( Table S4 ), as observed in several cancer cells in vitro [ 142 , 159 , 160 ] ( Table 2 ), thus configuring itself as a possible mutagen compound. This aspect is certainly to be taken into account in the evaluation of the toxicological profile of shikonin, even if it is worth noting that the antitumor activity of several anticancer drugs is based on DNA-damage induction [ 161 ]. In BALB/c nude mouse xenograft model of human osteosarcoma, shikonin reduced tumor growth, increased RIP1/3 expression, and reduced lung metastasis thus suggesting an antimetastatic activity for shikonin [ 138 ] ( Table S4 ).…”
Section: Necroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…In the same model, shikonin caused DNA damage [ 142 ] ( Table S4 ), as observed in several cancer cells in vitro [ 142 , 159 , 160 ] ( Table 2 ), thus configuring itself as a possible mutagen compound. This aspect is certainly to be taken into account in the evaluation of the toxicological profile of shikonin, even if it is worth noting that the antitumor activity of several anticancer drugs is based on DNA-damage induction [ 161 ]. In BALB/c nude mouse xenograft model of human osteosarcoma, shikonin reduced tumor growth, increased RIP1/3 expression, and reduced lung metastasis thus suggesting an antimetastatic activity for shikonin [ 138 ] ( Table S4 ).…”
Section: Necroptosismentioning
confidence: 99%
“…However, attention must be paid since the role of necroptosis in cancer metastatization is controversial. Strilic et al reported that tumor cells-induced necroptosis of endothelial cells promotes cancer cells extravasation and metastatization through interaction with DR6 (death receptor 6) [ 162 ], hence showing that necroptosis could promote cancer cell metastatization [ 161 ]…”
Section: Necroptosismentioning
confidence: 99%
“…Cytotoxic chemotherapy causes severe DNA damage directly by induction of breaks or indirectly due to the formation of reactive oxygen species (ROS) and ultimately induce cell death 34,35 . In responses to DNA damage, cells recruit DNA repair factors to upregulate mutagenic repair pathways that to maintain survival 36 .…”
Section: Discussionmentioning
confidence: 99%
“…To maintain genomic integrity of normal cells, damaged DNA induces checkpoints (e.g. p53-p21)-controlled cell cycle arrest until that DNA repair is achieved or cell death is launched (25). Under this premise, malignant cells might sustain in G0 phase by activating other epigenetics or genetics-dependent quiescence programs (26).…”
Section: Discussionmentioning
confidence: 99%